Traditional and Complementary Medicine (T&CM) Use and its Association with Diabetic Control among Diabetic Patients in a Tertiary Centre, Kuantan Pahang - Zainab ZA, Nurain; AR, Nur Syahirah; R, Nurtasneem; MF, Mohd Al-Baqlish; S, Mohd Ridzuan; MA, Edre (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Diabetes mellitus is a major global health concern worldwide. The fact that it is a lifelong chronic illness contributes to the increasing tendency of seeking traditional and complementary medicine (T&CM), yet study regarding this remains limited. This study aimed to measure the prevalence of T&CM use among diabetic patients and its association with diabetic control. MATERIALS AND METHODS: A cross sectional study was conducted at Hospital Tengku Ampuan Afzan (HTAA), Kuantan between July and August 2018. Following written consent, 136 type 2 adult diabetic patients in medical ward and those attending diabetic clinic were interviewed regarding the use of T&CM; and their blood investigation results were collected from patients’ medical records. A data collection form was used as study instrument. Descriptive statistic was used to measure the prevalence while chi-square test and independent t-test were used to find associations between T&CM use and study background and diabetic control. RESULTS: Low prevalence of T&CM use (16.9%) was found, predominated by retiree group (p<0.05). Majority of patients used T&CM as additional treatment for diabetes (60.9%) and the usage was influenced by friends, family members and advertisement. There was a significant difference in Glycosylated haemoglobin A1c (HbA1c) and Estimated Glomerular Filtration Rate (eGFR) levels between inpatient and outpatient T&CM users (p><0.05). CONCLUSION: 1 in every 6 diabetic patients in HTAA, Kuantan were using T&CM along with conventional diabetic medications in which retirees are predominated. No associations were found between T&CM uses and diabetic control. Outpatient T&CM users had lower HbA1c level with higher eGFR compared to inpatient users. ><0.05). Majority of patients used T&CM as additional treatment for diabetes (60.9%) and the usage was influenced by friends, family members and advertisement. There was a significant difference in Glycosylated haemoglobin A1c (HbA1c) and Estimated Glomerular Filtration Rate (eGFR) levels between inpatient and outpatient T&CM users (p<0.05). CONCLUSION: 1 in every 6 diabetic patients in HTAA, Kuantan were using T&CM along with conventional diabetic medications in which retirees are predominated. No associations were found between T&CM uses and diabetic control. Outpatient T&CM users had lower HbA1c level with higher eGFR compared to inpatient users.